Eye evolution: the blurry beginning - Nilsson, Dan-Eric; Arendt, Detlev (Current biology, 2008)
Recent work on the expression of retinal transcription factors and other molecular cues delivers interesting but partly contradictory information on the early phases of eye evolution.
Gesehen am 25.07.2017